Os gêneros orais: uma alternativa sócio-interacionista para o ensino da língua materna - Farias, Luana Francisleyde Pessoa de (2009)
This work is based on the discussion about space and the treatment offered to oral genres in the teaching of mother tongue from the studies of Bakhtin (2000, 2006), the teaching of language, developed by Dolz & Schneuwly and other employees of the School of Geneva (2004), and the research developed here in Brazil by researchers such as Rojo (2000, 2003) and Marcuschi (2003, 2005), who debate on the relationship between speech and writing. In this dissertation, we argue in favor of a teaching of oral genres that consider multimodality as a constituent of meaning construction of the speeches and reflections of social practices that make visible those meanings. We analyzed the factors that inhibit the expansion of the work with orality: the teacher who usually does not know the nature of the genre and is limited to instructions of the teaching material and textbooks which do not explore the socio-discursive aspects, but reduces this work to poor considerations and imprecise. The research, outlined here, constitutes an analysis of a collection of textbook of Portuguese for the second phase of the elementary school (6th to 9th grade) and oral interactions in classrooms during the development of activities provided for in that collection that addressed some aspect involving orality. This way, we found that the absence of work with oral genres in school, as teaching object, is due to the omission of the teaching material related to the nature and specificity of oral genres. But the textbook is still the mainly subsidy for the conduction of activities which, for oral teaching, is not according to the main demands of National Curriculum Parameters (1997, 1998). The research also showed that the greatest number of activities that involve oral practice prioritizes the writing form of oral or spontaneous oral discussion. After the analysis, we found that oral, formal, public and private genres are used merely as strategies for presentation of specific content and, therefore, by way of illustration, we present a didactic sequence, as an alternative to systematize this teaching.